Privacy Management on Instagram Users (Qualitative Descriptive Study of Surabaya's Early Adults in Security Management) - Aulia Putri Nur Aini; Syifa Syarifah Alamiyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to find out how to manage the privacy management by Instagram users. Disclosure of personal information on Instagram is a researcher's power to find out how Instagram users, especially early adults, manage privacy on social media, especially Instagram. This study uses the Communication Privacy Management theory developed by Sandra Petronio (2002), which states that everyone has a decision-making system regarding what information he thinks deserves to be shared with the public and which one should be kept for oneself. By using a case study research method in early adulthood in Surabaya using Instagram through interview and observation techniques, 7 informants were obtained in this study. The results obtained indicate that privacy management carried out by early Surabaya adults is in the form of providing information about self-identity such as name, age, year of birth, location, and profession written in the Bio account. In managing the privacy management of Instagram users, it also goes through the stage of private boundaries between public information that can be shared and which cannot be shared. Users also have control over the accounts they have which are intended so that they are not misused by irresponsible people. In addition, there are Instagram users who carry out management dialectics by thinking carefully about what will be shared on their respective Instagram accounts.